A Comparative In-vitro Study to Investigate the Role of Cavity Cleaning on Marginal Microleakage at Class II Cavities Restored by Composite (Journal of Hama University, 2024)
A comparative In-vitro study to investigate the role of cavity cleaning using Chlorhexidine 2% or Sodium hypochlorite 5.25% on marginal microleakage at class II cavities restored by Tetric N-Ceram composite by layering technique.30 Class II cavities (4×3×2 mm) were prepared in 15 extracted human molars, and distributed into 3 equal groups according to the disinfectants, as the group disinfected using water was considered a control group. The disinfectant was applied after etching and before applying Tetric N-Bond, then teeth were restored with Tetric N-Ceram composite. The specimens were subjected to a thermal cycling regimen 550 cycles. The dye penetration technique was adopted using blue methylene 2% to evaluate the rates of gingival microleakage, using a stereo microscope and ×40 magnification, then the statistical study was carried out by applying Kruskal-Wallis and Mann-Whitney tests at level of significance (P=0.05), using SPSS version 13.0.The marginal sealing of the composite restorations improved when disinfected with CHX 2%, which was significant compared with control group (P=0.012), while no significant differences were observed when disinfection using NaOCl 5.25% compared with control group (P=0.379), and compared with CHX 2% (P=0.090).It is preferable to disinfect the cavities using CHX 2% to reach a good margial seal at class II cavities restored by Tetric N-Ceram composite.